INTRAOCULAR PRESSURE AFTER PHACOEMULSIFICATION USING HYDROXYPROPYL METHYLCELLULOSE AND SODIUM HYALURONATE AS VISCOELASTICS - Waseem, Muhammad; Rustam, Naeem; Islam, Qamar ul (Journal of Ayub Medical College Abbottabad, 2007)
Background: Phacoemulsification and intraocular lens (IOL) implantation has resulted in early visual rehabilitation, increased wound stability and improved refractive results. Viscoelastic substances (VES) are important adjuncts in this type of surgery. Use of VES in phacoemulsification can be associated with adverse effects, the most common and potentially dangerous of which is the transient rise in intraocular pressure (IOP) in post-operative period. To evaluate the effects of viscoelastic substances on post-operative IOP after phacoemuls ification with implantation of intraocular lens, a cross-sectional comparative, prospective study was conducted in the department of Ophthalmology, Combined Military Hospital, Peshawar, Pakistan, from October 2003 to March 2004. Methods: One hundred patients were randomized into two groups of 50 each. Phacoemulsification with implantation of intraocular lens was performed in all the patients. 2% Hydroxypropyl Methylcellulose (HPMC) was used in one group and 1% Sodium Hyaluronate (NaHa) was used in the other group. IOP was measured pre-operatively as well as 24 hours and 7 days post-operatively. Results: There was no significant difference in the preoperative intraocular pressure between the two groups (p=0.483). Twenty four hours after surgery, the mean IOP increased by 2.84±SD 2.12 mm Hg in 2% Hydroxypropyl Methylcellulose group and 4.54±2.07 mm Hg in 1% Sodium Hyaluronate group. The increase was significantly higher in 1% Sodium Hyaluronate group as compared to 2% Hydroxypropyl Methylcellulose group (p=0.003). Seven days after surgery the mean intraocular pressure returned to near pre-operative levels in both the groups. Conclusion: Sodium Hyaluronate causes significantly higher increase in intraocular pressure in early post-operative period after cataract surgery inspite of maximum aspiration of viscoelastic substance from the eye following phacoemulsification surgery. Key Words: Intraocular pressure, Methylcellulose, Sodium Hyaluronate, Phacoemulsification, Viscoelastic substance.